Aspectual Fertility Variation and Its Effect on Gene Diversity of Seeds in Natural Stands of Taurus Cedar (Cedrus libani A. Rich.) - Nilüfer Yazici; Nebi Bilir (International Journal of Genomics)
There are many environmental and biological factors on forestry practices as known. Aspect called as slope faces is one of the most important environmental factors in these practices because of its easy application for managers. Fertility variation defined as an individual ability to give progeny and gene diversity estimated based on effective number of parents were investigated as the proportion of numbers of cones counted from individuals in natural stands sampled aspectual of Taurus cedar (Cedrus libani A. Rich.) for three consecutive years. The averages of cone number were 19.4, 47.2, and 75.5 for the years. It was the highest in flat (23.5) for 2013, in south (92.1) for 2014, and in flat (95.7) for 2015, while it was lowest in south (16.3), in east (18.2), and in north (39.4) for the years, respectively. Significant correlations (p≤0.01) were estimated among years for cone production in polled aspect. Estimated fertility variations changed for the years and stands. It could be generally acceptable level for typical natural stands except of west of 2014. Fertility variations were 1.55, 3.05, and 1.64 in polled stands for the years. Gene diversity was 0.99 for the years in polled stands. North aspect could be taken into consideration in establishment and selection of seed sources and gene conservation areas based on fertility variation and gene diversity.